Brain-IT: Targeting the brain using information technology for secondary prevention of mild neurocognitive disorder - Patrick Manser; Eling D. de Bruin (Bern Open Publishing, 2024)
Introduction A collaborative international guideline recommends physical exercise (PE) for the secondary prevention of mild neurocognitive disorder (mNCD; Veronese et al., 2023). PE is proposed to promote brain plasticity, maintain or increase cognitive reserve, and alleviate the pathological state in individuals with mNCD, which is characterized by an abnormal accumulation of proteins, excessive oxidative stress, metabolic disorder, and neuroinflammation within the brain (Lu et al., 2023). Individuals with mNCD often also have disrupted self-regulatory capacity to flexibly adapt to daily life challenges. This capacity is supported by the central autonomic network (CAN), which can be viewed as an integrated component of an internal regulatory system in which the brain controls visceromotor, neuroendocrine, and behavioral responses that are critical for goal-directed behavior, adaptability, and health (Thayer, 2009). To maximize the effectiveness of secondary prevention of mNCD, interventions should be designed to also target this network specifically. This could be achieved by combining motor-cognitive training with resonance breathing guided by heart rate variability biofeedback (HRV-BF). HRV-BF training aims to increase cardiac autonomic control, enhance homeostatic regulation, and regulate emotional state. It is effective in improving cardiac autonomic control, cognitive functioning (in particular executive functions), and emotional regulation (i.e., by decreasing symptoms of depression, anxiety, and stress) across different age groups and clinical populations (Laborde et al., 2022; Lehrer et al., 2020). Evidence also supports a causal role of cardiac autonomic control in modulating plasma Alzheimer's disease-related biomarkers (Min et al., 2023). Although HRV-BF has been suggested as a complementary treatment (Lehrer et al., 2020), its combination with motor-cognitive training remains to be investigated. Methods We systematically designed, developed, and evaluated a novel training concept (called 'Brain-IT') specifically for older adults with mNCD. It addresses the mechanism of action described above. The projects' methodology (Manser & de Bruin, 2021) followed the guidelines of the Medical Research Council for the development and evaluation of complex interventions as well as the Multidisciplinary Iterative Design of Exergames (MIDE) - Framework. The Brain-IT project was structured in three phases. In phase 1, we systematically combined a comprehensive literature synthesis (Manser & de Bruin, 2021) with qualitative research including primary end users (older adults with mNCD), secondary end users (physiotherapists, occupational therapists, healthcare professionals), exergaming researchers, as well as experts from the exergaming industry (Manser et al., 2023) to specify a set of design requirements for the Brain-IT training concept. In phase 2, possible concepts were co-designed and elaborated based on the set of design requirements defined in phase 1. The first prototype of the resulting Brain-IT training concept (Manser & de Bruin, 2021) then entered the iterative cycle of feasibility, usability, safety, and acceptance testing and integrating study results for further development based on co-design until an "acceptable" solution was achieved. In this regard, we conducted a pilot randomized controlled study (RCT) including 18 individuals with mNCD. (Manser et al., 2023) Finally, in phase 3, the effectiveness of the addition of the Brain-IT training to usual care to improve global cognitive functioning is investigated in a RCT including 41 individuals with mNCD (study protocol: Manser et al., 2023). As secondary objectives, the effects of the Brain-IT training on: (1) domain-specific cognitive functioning, (2) spatiotemporal parameters of gait, (3) instrumental activities of daily living and (4) psychosocial factors (i.e. quality of life, and levels of depression, anxiety, and stress), and (5) cardiac vagal modulation are explored. Additionally, brain structure and function is evaluated by magnetic resonance imaging to explore underlying neural changes of the training in relation to adaptations in cognitive performance. Results Ten secondary end users, exergaming researchers, and experts from the exergaming industry (80% females) and eight older adults with mNCD (38% females) contributed to the qualitative research (Manser et al., 2023) which allowed us to successfully integrate all the acquired knowledge of phase 1 to determine a set of design requirements (Manser & de Bruin, 2021). This set of design requirements built the basis for phase 2, where we developed a first prototype of the Brain-IT training concept. Our reflections on the design considerations and our proposed solutions are summarized in (Manser & de Bruin, 2021; Manser et al., 2023). The Brain-IT training concept represents a guideline for applying a combination of exergame-based motor-cognitive training and HRV-BF training by standardizing the training characteristics as well as the structure and content of training and can be implemented with different hardware and software solutions. For an overview, the Brain-IT training consists of a personalized and individually adapted multi-domain exergame-based simultaneous motor-cognitive training with incorporated cognitive tasks combined with HRV-BF training. It is adopted with a deficit-oriented focus on the neurocognitive domains of (1) learning and memory, (2) executive function, (3) complex attention, and (4) visuospatial skills. Each participant is instructed to train ≥ 5x/week for ≥ 24 min per session resulting in a weekly training volume of ≥120 min. All training sessions are planned to take place at participants' homes. In this project, we used technology of Dividat AG, Polar, and Kubios Oy to implement our training concept. In the pilot RCT we showed that Brain-IT training is feasible (mean adherence and compliance rates of 85.0 and 84.1%, respectively) and usable (mean system usability scale = 71.7 ± 15.4). In addition, high levels of exergame enjoyment, an increase in exergame enjoyment, and internalization of training motivation with large effect sizes (p = 0.03, r = 0.75 and p = 0.03, r = 0.74, respectively), as well as acceptable perceived usefulness were observed. Phase 3 is ongoing. To date, 41 participants were included into the study, of which two withdrew consent before pre-measurements, two dropped-out during intervention (one in each group), and 29 (72.6 ± 9.3 years; 24.1% females) successfully completed the study. Preliminary data suggest significant effects with large effects sizes in favor of the intervention group for global cognitive functioning (F(1, 29) = 4.692, p = 0.039, partial η2 = 0.153) as well as immediate (F(1, 29) = 6.501, p = 0.018, partial η2 = 0.213) and delayed (F(1, 29) = 5.227, p = 0.031, partial η2 = 0.179) verbal recall. The remaining (underpowered) statistical analyses revealed no significant effects, but favorable changes in descriptive statistics with small to moderate effects in favor of the intervention group, especially with regards to quality of life. Discussion/Conclusion The development of novel (exergame-based) training concepts is greatly facilitated when it is based on a theoretical framework. Applying the MIDE-framework resulted in a structured, iterative, and evidence-based approach that led to the identification of multiple key requirements for the exergame design as well as the training components that otherwise may have been overlooked or neglected. This resulted in a user-centered, personalized, and highly innovative training concept that is feasible, usable, and highly accepted by individuals with mNCD. Preliminary data regarding the effectiveness of the intervention is promising, suggesting that the training significantly improved global cognitive functioning, verbal immediate, and delayed recall with large effect sizes, and tends to be beneficial in improving quality of life. To be able to conclude about the effectiveness of the Brain-IT training concept, a full-scale confirmatory randomized controlled superiority trial is warranted. References Laborde, S., Aelle, M. S., Borges, U., Dosseville, F., Hosang, T. J., Iskra, M., Mosley, E., Salvotti, C., Spolverator, L., Zammit, N., & Javelle, F. (2022). Effects of voluntary slow breathing on heart rate and heart rate variability: A systematic review and a meta-analysis.